Вибрирующая струна для измерения профиля тонких пучков в ускорителях: предварительные тесты на лазерном пучке - Э. Г. Лазарева (ՀՀ ԳԱԱ հրատ.)
The possibility to use a vibrating wire as a target in the method of scanning of transverse profiles of thin beams in accelerators has been studied. In the case where the transverse dimensions of the beam are comparable to the amplitude of oscillations of the wire, the vibrating wire can be used for a fast measurement of the transverse beam profile without moving the sensor. The scanning procedure is replaced by the use of the wire movement during its mechanical oscillations. The method is tested on a focused beam of a semiconductor laser with a spot size at the focus of ~0.1 mm. The reconstruction of the transverse profile is performed on the basis of the measurements of the photons reflected from the vibrating wire by using fast photodiodes.
Keywords: Physics; Science; Radiophysics